Short-term effects of lower-extremity heavy resistance versus high-impact plyometric training on neuromuscular functional performance of professional soccer players - Boraczynski, M.; Magalhães, J.; Nowakowski, J. J.; Laskin, J. J. (Sports, 2023)
Background: To compare the effects of short-term 8 week heavy-resistance or plyometric training protocols (HRT or PLY) incorporated into regular soccer practice on measures of neuromuscular functional performance in professional soccer players, a single-blind randomized controlled trial was conducted. Methods: Forty-seven participants aged 22.3 ± 3.52 years were assigned to three groups: HRT (n = 15), PLY (n = 15), and control (CON; n = 17). The HRT group performed 3 sets and 10 repetitions twice a week using 80% of their baseline 1-RM (weeks 1-3), followed by 8 repetitions at 85% 1-RM (weeks 4-6), and 6 repetitions at 90% 1-RM (weeks 7-8) of 6 lower-body strength exercises with a 1 min rest period between sets. The PLY protocol involved a preparatory phase (weeks 1-2), followed by two 3-week progressive periods (weeks 3-5 and weeks 6-8). The plyometric sessions consisted of four jump exercises/drills with progressively increasing number of sets and total number of foot contacts. The rest intervals between repetitions and sets were 15 and 90 s, respectively. Outcome measures included tests assessing 10 and 30 m speed (t10m and t30m), one-repetition maximum half-back squat (1-RM squat), isokinetic peak torques for the quadriceps and hamstring muscles (Qcon and Hcon), countermovement jump (CMJ), and squat jump (SJ). Results: Two-way ANOVA detected main effects of time and group×time interactions for all examined variables, except t30m, 1-RM, and relative 1-RM. Post hoc analyses revealed significant increases in the HRT group (t10m: 6.3%, t30m: 7.1%; absolute 1-RM: 29.6%; relative 1-RM: 30.3%, Qcon: 24.5%; Hcon: 14.4%; CMJ: 5.9%; SJ: 7.2%, all p < 0.001) and the PLY group (t10m: 3.1%; t30m: 4.1%; absolute 1-RM:19.1%; relative 1-RM: 20.3%; Qcon: 12.6%; Hcon: 8.7%; CMJ: 3.3%; SJ: 3.5%, all p < 0.001). HRT was superior compared to PLY in relative 1-RM, Qcon and Hcon (all p < 0.001). In addition, we found knee muscular strength imbalance in 70.5% of participants from the total sample (H/Q ratio < 60%). The HRT and PLY protocols resulted in improved neuromuscular functional performance compared to the regular soccer regime. Conclusions: This study showed that during the pre-competitive season, additional HRT and PLY drills/exercises as a substitute for standard soccer training as part of a regular 90 min practice twice a week for 8 weeks, can produce acute physical performance-enhancing effects in professional soccer players.